2015
DOI: 10.1538/expanim.14-0097
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus B3 infection reduces female mouse fertility

Abstract: Previously we demonstrated coxsackievirus B3 (CVB3) infection during early gestation as a cause of pregnancy loss. Here, we investigated the impacts of CVB3 infection on female mouse fertility. Coxsackievirus-adenovirus receptor (CAR) expression and CVB3 replication in the ovary were evaluated by immunohistochemistry or reverse transcription-polymerase chain reaction (RT-PCR). CAR was highly expressed in granulosa cells (GCs) and CVB3 replicated in the ovary. Histological analysis showed a significant increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In cattle, bovine diarrhea (Grooms et al, 1998) and bovine pestivirus (McGowan et al, 2003) have also been found in the ovaries, with the latter a known etiological factor of ovarian dysfunction. In mouse models, Zika virus acutely infects the ovaries and causes inflammation with no consequences for fertility (Caine et al, 2019), Coxsackie virus B infection increases the number of atretic follicles (Shim et al, 2015), whereas vaccinia virus infection destroys ovarian tissue and renders mice infertile (Karupiah et al, 1990). HCMV has been implicated as an etiological factor in early pregnancy loss (Gabrielli et al, 2009;Grammatikopoulou et al, 2012;Iwasenko et al, 2011;Warner et al, 2012) and has been detected in ovaries and fallopian tubes (Clarke et al, 1997;Iwasaki et al, 1988;Sharma et al, 1994), but again, no data are available regarding the mechanisms or potential long-term fertility problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cattle, bovine diarrhea (Grooms et al, 1998) and bovine pestivirus (McGowan et al, 2003) have also been found in the ovaries, with the latter a known etiological factor of ovarian dysfunction. In mouse models, Zika virus acutely infects the ovaries and causes inflammation with no consequences for fertility (Caine et al, 2019), Coxsackie virus B infection increases the number of atretic follicles (Shim et al, 2015), whereas vaccinia virus infection destroys ovarian tissue and renders mice infertile (Karupiah et al, 1990). HCMV has been implicated as an etiological factor in early pregnancy loss (Gabrielli et al, 2009;Grammatikopoulou et al, 2012;Iwasenko et al, 2011;Warner et al, 2012) and has been detected in ovaries and fallopian tubes (Clarke et al, 1997;Iwasaki et al, 1988;Sharma et al, 1994), but again, no data are available regarding the mechanisms or potential long-term fertility problems.…”
Section: Discussionmentioning
confidence: 99%
“…We identified and characterized multiple barriers of innate immunity that prevented infection of FG cells in nonpregnant animals, efficiently safeguarding the oocytes and maintaining fertility of the host. Indeed, viral infections that cause infertility in humans or experimental animals are associated with infection of FG cells (An et al, 2017;Karupiah et al, 1990;Shim et al, 2015;Wang et al, 2016). Thus, understanding how this scenario is avoided during infection with natural pathogens such as CMV broadens our understanding of virus and host coevolution and may offer insights into mechanisms of infertility.…”
Section: Introductionmentioning
confidence: 99%